Revisiting rhetoric in the era of politicized media and mediatized politics interview with Emeritus Professor Herbert W. Simons of Temple University - Ragragio, Jefferson Lyndon D. (2017)
Access online through this link: https://www.plarideljournal.org/article/revisiting-rhetoric-era-politicized-media-mediatized-politics-interview-emeritus-professor-herbert-w-simons-temple-university
Keywords: Simons, Herbert W. -- Interviews; Mass media and politics